2021
DOI: 10.1016/j.jcyt.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Multisite studies for validation and improvement of a highly efficient culture assay for detection of undifferentiated human pluripotent stem cells intermingled in cell therapy products

Abstract: Background aims: The Multisite Evaluation Study on Analytical Methods for Non-Clinical Safety Assessment of Human-Derived Regenerative Medical Products (MEASURE) is a Japanese experimental pub-licÀprivate partnership initiative, which aims to standardize methodology for tumorigenicity evaluation of human pluripotent stem cell (hPSC)-derived cell therapy products (CTPs). Undifferentiated hPSCs possess tumorigenic potential, and thus residual undifferentiated hPSCs are one of the major hazards for the risk of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Since highly sensitive hiPSC detection methods using LIN28A , ESRG , CNMD and SFRP2 as hiPSC markers have been reported for retinal pigment epithelial cells [ 13 ], dopaminergic progenitor cells [ 11 ], cardiomyocytes [ 14 ], T cells [ 15 ] and liver bud [ 20 ], we analyzed the expression of these four genes in public RNA-seq datasets of various human fetal tissues [ 21 ] using GREIN [ 22 ]. We found similarly low expressions of LIN28A in the fetal kidney, liver, and pancreas as in the heart and similarly low expressions of CNMD and SFRP2 in the kidney and pancreas as in the liver ( S1A Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since highly sensitive hiPSC detection methods using LIN28A , ESRG , CNMD and SFRP2 as hiPSC markers have been reported for retinal pigment epithelial cells [ 13 ], dopaminergic progenitor cells [ 11 ], cardiomyocytes [ 14 ], T cells [ 15 ] and liver bud [ 20 ], we analyzed the expression of these four genes in public RNA-seq datasets of various human fetal tissues [ 21 ] using GREIN [ 22 ]. We found similarly low expressions of LIN28A in the fetal kidney, liver, and pancreas as in the heart and similarly low expressions of CNMD and SFRP2 in the kidney and pancreas as in the liver ( S1A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Avoiding hiPSC contamination or residual hiPSCs requires a thoroughly controlled cell manufacturing process and assays that ensure the absence of hiPSCs. Several in vitro tests for this purpose exist [ 10 12 ], including flow cytometry [ 13 ], quantitative RT-PCR (qRT-PCR) [ 13 ], droplet digital PCR (ddPCR) [ 14 , 15 ], culture methods for efficient hiPSC growth [ 15 , 16 ], the detection of marker molecules released into the culture medium [ 17 , 18 ], and enrichment using magnetic beads [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This assay can detect colonies formed from iPSCs using a highly efficient culture system, which favours the growth of iPSCs, and the limit of detection (LOD) has been reported to be 0.001% 27 . In addition, this assay has been improved with a sorting system, and the LOD was reportedly 0.0002% 9 . The disadvantages of this assay are it requires 1 week and a large amount of samples used for test.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to remove unexpected cells such as undifferentiated cells from iPSC-derived target differentiated cells 3 6 . Most of the existing quality control tests for detecting undifferentiated cells in iPSC-derived products involve crushing of cells 3 , 4 , 7 9 ; as a result, the cells to be transplanted cannot be tested directly, which in turn increases the cost of the procedure. Current commonly used methods to detect residual undifferentiated cells are as follows: detecting undifferentiated cell-specific protein using flow cytometry, measuring the levels of Lin -28 Homolog A ( LIN28A ), and colony formation assay (CFA) 2 , 7 ; however, they require cells for testing.…”
Section: Introductionmentioning
confidence: 99%
“…Artyuhov et al showed that the detection limit of OCT4 , TGDF , and LIN28 was 0.01%, whereas that with ddPCR was 0.002% 94 . Watanabe et al reported a detection efficiency of 0.00002% when ddPCR was performed after enrichment of stem cell markers using magnetic beads 97 . In addition, it has been reported that the detection efficiency of hPSCs in hPSC‐CMs suggests that ddPCR is more suitable than qPCR for the assessment of residual undifferentiated hPSCs.…”
Section: In Vitro Tumorigenicity Tests For Hpsc‐derived Productsmentioning
confidence: 99%